A COMMENT ON “THE FEDERAL HOME LOAN BANK SYSTEM AND THE CONTROL OF CREDIT” - Haywood, Charles F. (Journal of Finance, 1958)
In “the Federal Home Loan Bank System and the Control of Credit” (Journal of Finance, XII [1957], 319–32), Gordon W. McKinley set forth an erroneous analysis in support of the view that there is little or no need for the monetary authorities to exercise greater control over savings intermediaries. The principal errors in his analysis can be demonstrated by reconsidering the three questions he sought to answer (p. 320). Defining money as “anything which is normally, consistently, and generally used as a store of value and/or a medium of exchange” (p. 321), McKinley answered this question in the negative. What McKinley defined, however, is not money but assets. The unique property of money is that it serves as a store of value and as a medium of exchange. It is true that all stores of value which do not serve as means of payment are, in varying degrees, substitutes for holding money, but it is unnecessary and actually extirpatory of correct analysis to include these substitutes in the concept of money. If the concept of money is not restricted to those things serving as a medium of exchange, the concept of the velocity of the circulation of money, which McKinley misapprehended but did not abandon in his analysis, loses its significance. One can speak of time deposits, savings and loan shares, etc., as having a certain “rate of turnover,” but this is not the same concept as the velocity of the circulation of money. Time deposits and other savings claims turn over against money. In the same sense one can speak of the rate of turnover of inventories, real estate, used cars, or any other non-money asset. The turnover of money and the turnover of time deposits, savings and loan shares, and other non-money assets are obverse phenomena. Savings intermediaries, including the savings departments of commercial banks, do exert a quantitative effect upon monetary magnitudes. However, this effect is not on the quantity of money, as McKinley contended, but on the velocity of the circulation of money. By issuing very liquid substitutes for holding money, savings intermediaries make it quite easy for spending units to vary their ratios of total outlays to money balances. McKinley's analysis not only failed to delineate this velocity effect but actually obscured it, because of his incorrect definition of money. It is one thing to show that savings intermediaries are not free of Federal Reserve influence and quite another thing to show that the Federal Reserve can control these intermediaries so that their operations are not destabilizing. McKinley drew the latter conclusion, although his arguments (pp. 325–28) demonstrated only the former. In the face of a tight-money policy, savings intermediaries may find, as McKinley argued, that it is more difficult to induce spending units to give up demand deposits in exchange for savings claims, but a tight-money policy also raises yields on earning assets, thereby providing savings intermediaries with the means and incentive for more aggressive expansion of liabilities. Far from exercising effective control over the total of liabilities of savings intermediaries, Federal Reserve policy may contribute to destabilizing changes in the rate of expansion of the liabilities and, hence, the lending capacity of savings intermediaries. There is more reason to believe that Federal Reserve policy may influence the composition of assets of savings intermediaries than the total of their assets and liabilities, but even here the evidence is not nearly so conclusive as McKinley asserted. The decline in security prices associated with a tight-money policy may make savings intermediaries less willing to shift from securities to loans, but does this effect do any more than temper a strong, destabilizing shift? Effective control must surely go beyond the partial mitigation of destabilizing forces. It would have been helpful if McKinley had documented his allusion to the “clear statistical evidence in studies made by the Federal Reserve Board.” McKinley gave an affirmative answer to the first part of this question and a qualified negative answer to the second part, but unfortunately he failed to pose here the really pertinent question. That the Federal Home Loan Banks create certain deposit balances which members use as a means of payment is not crucial to the issue of whether their policies should be “consciously co-ordinated” with Federal Reserve policies. The relevant point is that, by making advances to members, the Federal Home Loan Banks provide a source of marginal liquidity in much the same way and with much the same effects as any central bank performing the function of lender of last resort. By varying the cost and availability of advances, the Federal Home Loan Banks not only alter the distribution of lendable funds but also affect the capacity of the entire financial system to hold debt, i.e., its capacity to generate lendable funds. McKinley conceded that in recent years the Federal Home Loan Banks “may have been motivated by a desire to exercise selective control over credit flows” and that “such use of their powers appears to be beyond the compass of legislation establishing the Banks and suffers also from the difficulty of co-ordination with Federal Reserve policy” (p. 332). What McKinley failed to recognize even in this regard, however, is that, whether or not the Federal Home Loan Banks are “motivated by a desire to exercise selective control,” they must at all times have some conscious policy with respect to the cost and availability of advances to members, and such policy, whatever it may be, has an effect upon the distribution of lendable funds. Over and above this qualitative effect, the operations of the Federal Home Loan Banks have a quantitative effect, because the banks are part of the mechanism determining the capacity of the financial system to generate lendable funds and to alter the velocity of the circulation of money. To attempt to measure the importance of the Federal Home Loan Banks in this regard would extend these remarks beyond the space limitations of this comment. Whether the quantitative aspects of the operations of the Federal Home Loan Banks should be consciously co-ordinated with Federal Reserve policy is part of the broader problem of controlling changes in the velocity of the circulation of money. It would be presumptuous to attempt within the space limitations of a comment to make a case that the Federal Reserve should have greater control of savings intermediaries. One thing is clear, however, McKinley's approach is not the way to demonstrate that such control is not necessary.